THE URGENCY OF LEGAL REGULATIONS REGARDING ASSET CONFISCATION IN CORRUPTION CRIMES AS AN EFFORT TO RECOVER STATE LOSSES - Rihanda Shalsabilla Tanjung; Mhd. Teguh Syuhada Lubis (Inspiring Law Journal, 2025)
Indonesia faces corruption as an extraordinary crime that undermines economic stability and democratic values. Current law enforcement still tends to use a conventional approach, emphasizing corporal punishment rather than restitution of state losses. Consequently, the recovery of assets obtained from corruption is less than optimal due to weak evidence and asset tracking processes. Based on these issues, this study formulates three issues: how to enforce the law on corruption crimes, the urgency of regulating asset confiscation as an effort to recoup state losses, and the criminal law policy regarding asset confiscation in corruption crimes.This research employs a normative legal method with a statute approach. The research is descriptive and analytical in nature, utilizing secondary data in the form of primary, secondary, and tertiary legal materials. Data were collected through literature review and analyzed qualitatively to provide systematic solutions.The research findings show that corruption law enforcement in Indonesia still relies on a follow-the-suspect approach rather than a follow-the-money approach. The current asset confiscation mechanism (in personam) has limitations, particularly when the defendant dies or flees, thus hampering the recovery of state losses. Therefore, there is an urgency to pass the Asset Forfeiture Bill to adopt a more progressive and asset-oriented non-conviction-based asset forfeiture (NCB) mechanism. Future criminal law policy must integrate penal and non-penal approaches so that asset confiscation becomes the primary instrument for recovering state losses, as initially accommodated in the new Criminal Code.